Speed distribution on high-speed highways - Nor Mastura Daud, 1994-, author; Othman Che Puan, supervisor; Azman Mohamed, 1972-, supervisor; Fakulti Kejuruteraan Awam (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Project Paper (Sarjana Muda Kejuruteraan (Awam) - Universiti Teknologi Malaysia, 2018